1999
DOI: 10.1007/s002130050818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous oral nicotine administration on brain nicotinic receptors and responsiveness to nicotine in C57Bl/6 mice

Abstract: The route of drug delivery is an important consideration in studies that evaluate the long-term bio-behavioral adaptations that occur in response to chronic drug administration. Continuous infusions (intravenous or subcutaneous) or intermittent intraperitoneal (or subcutaneous) injections are the most commonly utilized routes of chronic drug delivery in these studies. The purpose of the present study was to determine the effects of chronic oral nicotine exposure on sensitivity to nicotine and brain nicotinic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
134
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(152 citation statements)
references
References 29 publications
15
134
3
Order By: Relevance
“…Accordingly, future studies on the biological bases of ethanol and nicotine interactions are necessary and the use of other strains and species may provide valuable data. Though nicotine concentration may seem high in the drinking solution, nicotine absorption from the buccal cavity yields cotinine plasma levels (Klein et al, 2003(Klein et al, , 2004Sparks and Pauly, 1999) comparable to those found in adolescent smokers (Binnie et al, 2004;Caraballo et al, 2004;Wood et al, 2004). As for ethanol, according to previous studies in adolescent rodents, even the moderate doses used in the present study result in blood levels well above the legal driving limit (Silveri and Spear, 2000).…”
Section: Methodological Issuessupporting
confidence: 76%
See 2 more Smart Citations
“…Accordingly, future studies on the biological bases of ethanol and nicotine interactions are necessary and the use of other strains and species may provide valuable data. Though nicotine concentration may seem high in the drinking solution, nicotine absorption from the buccal cavity yields cotinine plasma levels (Klein et al, 2003(Klein et al, , 2004Sparks and Pauly, 1999) comparable to those found in adolescent smokers (Binnie et al, 2004;Caraballo et al, 2004;Wood et al, 2004). As for ethanol, according to previous studies in adolescent rodents, even the moderate doses used in the present study result in blood levels well above the legal driving limit (Silveri and Spear, 2000).…”
Section: Methodological Issuessupporting
confidence: 76%
“…C57BL/6 mice were chosen because prior reports demonstrate that adult and periadolescent mice from this strain consume nicotine in the concentration used in the present study. In fact, oral nicotine has also been shown to be effective in eliciting behavioral (Adriani et al, 2002(Adriani et al, , 2004Gaddnas et al, 2001) and neurochemical alterations, including nicotinic receptors upregulation (Nuutinen et al, 2005;Sparks and Pauly, 1999), altered monoamine levels, and metabolism (Gaddnas et al, 2000;Tammimaki et al, 2006;Vihavainen et al, 2006) as well as altered expression of genes implicated in synaptic plasticity induced by drugs of abuse (Marttila et al, 2006) and in Alzheimer's disease (Gutala et al, 2006) in this and other mouse strains. This strain of mice is known to present particular features, such as higher voluntary ethanol consumption (Crawley et al, 1997), which should be taken into consideration in studies that involve the administration of this substance, even though the bases underlying these strain-specific characteristics remain poorly understood (Crabbe et al, 1999).…”
Section: Methodological Issuesmentioning
confidence: 91%
See 1 more Smart Citation
“…In the drinking water of treatment and control groups, 2% saccharine was added (to mask the bitter flavor of nicotine) (Salas et al, 2009;Sparks and Pauly, 1999;Zhang et al, 2012). In coadministration experiments, mice received ethanol or control injections during the last 10 days of nicotine treatment.…”
Section: Nicotine and Ethanol Cotreatmentmentioning
confidence: 99%
“…Therefore, since cerebral a7 nAChRs are normally upregulated in heavy smokers (Benwell et al, 1988;Breese et al, 2000) and after chronic nicotine administration in animals (Olale et al, 1997;Sparks and Pauly, 1999), a7 nAChRs in patients appear to have an abnormally blunted reaction to excessive smoking. This could be due to a dysfunction in any of several distinct endogenous mechanisms, which normally control a7 nAChR expression and activity in the brain (Albuquerque et al, 1997;Pereira et al, 2002).…”
Section: Introductionmentioning
confidence: 99%